1998
DOI: 10.1540/jsmr.34.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excess K+ on Carbachol-induced Contractions in the Guinea-Pig Tracheal Muscle.

Abstract: Abstract1. In smooth muscles isolated from the guinea-pig trachea, the effects of dihydropyr idines, nifedipine and nicardipine on contractions produced by carbachol (Cch) were studied in normal (6mM) and excess K+ concentration (60mM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…ASM in general maintains a relatively low intracellular calcium concentration under resting conditions (Jude et al, 2008), thus, providing a reasonable explanation for the major contribution of extracellular Ca 2+ in carbachol-induced contraction in rat trachea. This observation is consistent with a study previously done on guinea-pig trachea (Takemoto et al, 1998), who also reported that carbachol-induced contraction was not affected by thapsigargin.…”
Section: Discussionsupporting
confidence: 93%
“…ASM in general maintains a relatively low intracellular calcium concentration under resting conditions (Jude et al, 2008), thus, providing a reasonable explanation for the major contribution of extracellular Ca 2+ in carbachol-induced contraction in rat trachea. This observation is consistent with a study previously done on guinea-pig trachea (Takemoto et al, 1998), who also reported that carbachol-induced contraction was not affected by thapsigargin.…”
Section: Discussionsupporting
confidence: 93%
“…15 These Ca 2+ pathways on the cell surface and the endoplasmic membrane contribute to an increase in [Ca 2+ ] i . 16 Because depolarization inhibits ROCC‐mediated Ca 2+ influx in guinea‐pig tracheal muscle, 7 the effects of membrane depolarization to potentiate or attenuate muscle tension generated by an agonist are likely to depend on the balance between Ca 2+ influx through ROCC and Ca 2+ release. In the present study, Ca 2+ ‐induced contractions of the smooth muscle pretreated by PGE 2 were concentration‐dependently potentiated by high K + and TEA in the absence of verapamil and inhibited in its presence, suggesting that VOCC‐mediated Ca 2+ influx should contribute predominantly to the elevation of [Ca 2+ ] i in depolarized cells.…”
Section: Discussionmentioning
confidence: 99%
“… 5,6 However, the mechanisms underlying ROCC inhibition by depolarization are still controversial in guinea‐pig tracheal muscle. 7 The Ca 2+ influx and receptor‐mediated inositol 1,4,5‐triphosphate (IP 3 )‐production trigger Ca 2+ ‐induced Ca 2+ release (CICR) and IP 3 ‐induced Ca 2+ release (IICR) from sarcoplasmic reticulum (SR), respectively, leading to further membrane depolarization, which subsequently causes more VOCC activation. 8 Because of the positive feedback mechanism via VOCC‐mediated Ca 2+ influx, it is hard to observe direct effects of membrane depolarization on Ca 2+ signalling.…”
Section: Introductionmentioning
confidence: 99%